The interactions between nisoldipine and two beta-adrenoceptor antagonists--atenolol and propranolol. - Elliott, H L (1991)
1. The interactions between the dihydropyridine calcium antagonist nisoldipine and two beta-adrenoceptor blocker drugs (atenolol and propranolol) were investigated in two groups of healthy normotensive subjects. 2. The steady state plasma concentrations of both beta-adrenoceptor blockers were significantly altered by the addition of nisoldipine: for propranolol there were significant increases in Cmax, by about 50%, and in AUC by about 30% and for atenolol there was a significant increase in Cmax, by about 20%. 3. The addition of nisoldipine was also associated with significant changes in apparent liver blood flow (measured by indocyanine green clearance) from 1.4 to 2.4 l min-1 in the atenolol group and from 1.3 to 2.3 l min-1 in the propranolol group. 4. Both nisoldipine-beta-adrenoceptor blocker combinations were associated with small enhanced blood pressure reductions e.g. from 104/60 with atenolol alone to 98/50 mm Hg with the combination but there was no alteration to the extent of beta-adrenoceptor blockade (as assessed by bicycle ergometry). 5. This pharmacodynamic profile in healthy normotensives is consistent with the known therapeutic efficacy of such combination treatments in patients with hypertension and angina. 6. It is suggested that there is a pharmacokinetic component to the efficacy of this type of combination, perhaps reflecting vasodilator-induced changes in drug absorption and/or hepatic extraction.